Yankees and Rebels stories of U.S. Civil War leaders - Otfinoski, Steven (North Mankato, Minnesota Capstone Press, 2015)
"Powerful leaders emerged during the victories and defeats of the Civil War. Meet the people who planned the battles, led the attacks, and shaped the war between the Yankees and the Rebels. Perfect for Common Core studies on analyzing multiple accounts of an event"--
A gift from book Africa
Famous people
1 2 13 15
Keywords: United States -- History -- Civil War, 1861-1865 -- Biography -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Biography; United States